Pemetaan Persebaran Startup Digital dalam Penerapan Society of Creativity di Indonesia Berbasis WebGIS: Array - Andriana, Septiana Dewi; Hasdiana, Hasdiana (Universitas Harapan Medan, 2022)
Starter companies or technology-based startups or better known as Digital Startups have been booming in many countries, especially in Indonesia in recent years. Various ideas and solutions are offered to be a way out of a problem that is often faced by the community. Incubators, Investors and even the Government are also competing to provide digital Startup development programs, because of this many digital startups have sprung up and started to develop in Indonesia such as its predecessors, namely GoJek, Bukalapak, Tokopedia, and Tiket.com which have become Unicorns. even Decacorn in Indonesia. The mapping of the distribution of the Digital Startup itself needs to be done so that the application of a creative society or the Society of Creativity can be carried out in Indonesia, especially in the current Era 5.0 Society. Geographic Information System is a platform that provides management of spatial data (spatial data) and non-spatial data (attribute data) that can be used to map specific case studies to achieve a specific goal. At present Geographic Information Systems can be developed based on Web or WebGIS. The mapping of the distribution of Digital Startups in Indonesia is currently carried out to facilitate the Government in monitoring and developing the number of digital startups in Indonesia, so that people who are capable of being competitive and creative can be formed in Indonesia because they are always monitored and well developed by the Government. Research on Mapping the Distribution of Digital Startups in the Implementation of the Society of Creativity in Indonesia is based on WebGIS. The editor that will be used is ArcGIS Online.